(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
Over the next thirty years, the renaissance in psychedelic research for psychotherapy and the burgeoning possibilities of blockchain technologies will come together. Describing fascinating interactions that are already taking place, the author suggests further possibilities for these two technologies relevant to psychotherapists and academics and outlines links to existential philosophy.